2000
DOI: 10.1038/sj.mp.4000735
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E is a genetic risk factor for fetal iodine deficiency disorder in China

Abstract: Fetal iodine deficiency disorder (FIDD) is the principal form of endemic cretinism, and the most common cause of preventable mental deficiency in the world. However not everyone at risk develops FIDD and familial aggregation is common. This suggests that genetic factors may also be involved. The Apolipoprotein E (APOE) gene encodes for a lipoprotein that possesses a thyroid hormone binding domain, and APOE genotype may affect the efficiency with which thyroid hormone influences neuronal cell growth during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…However, E4 has been found to be a risk factor for fetal iodine deficiency in the Chinese population. It has been proposed that this phenomenon may affect population selection and contribute to the low frequency of E4 in Chinese versus Caucasian populations [Wang et al, 2000]. In the present study, there was an underrepresentation of E4 in females relative to males as previously reported [Moalem et al, 2000].…”
Section: Discussionsupporting
confidence: 76%
“…However, E4 has been found to be a risk factor for fetal iodine deficiency in the Chinese population. It has been proposed that this phenomenon may affect population selection and contribute to the low frequency of E4 in Chinese versus Caucasian populations [Wang et al, 2000]. In the present study, there was an underrepresentation of E4 in females relative to males as previously reported [Moalem et al, 2000].…”
Section: Discussionsupporting
confidence: 76%
“…The reason and consequences of this phenomenon are still unclear. Moreover, as described by Wang et al [59], the APOE genotype may affect the influence of thyroid hormone on neuronal cell growth during the first and second trimesters of fetal development. They suggested that in iodine-deficient areas, the presence of the APOE ε4 allele is a genetic risk factor for the development of fetal iodine deficiency disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide iodine deficiency is the leading cause of preventable MR and its elimination is within reach with enormous benefits [Delange et al, 2001]. Moreover Chinese studies show that genetic factors may also underly the susceptibility to iodine deficiency [Wang et al, 2000]. In the meantime, epidemiological data relating to MR in China with its 1.3 billion population are limited [Sonnander and Claesson, 1997].…”
Section: Social Classmentioning
confidence: 99%